Resveratrol Protects Against Methotrexate-Induced Hepatic Injury in Rats - (:unkn) unknown (CANADIAN SOC PHARMACEUTICAL SCIENCES, 2010)
Purpose. The aim of this study was to investigate the possible protective effect of resveratrol on some liver and blood parameters in methotrexate (MTX) induced toxicity in rats. MTX is used widely to treat various neoplastic diseases such as acute lymphoblastic leukemia, lymphoma, solid cancers, and autoimmune diseases. We hypothesized that resveratrol has a potential to decrease the oxidant damage in MTX-induced hepatic injury. Methods. Following a single dose of methotrexate (20 mg/kg, i.p.), either saline or resveratrol (10 mg/kg, orally) was administered for 5 days. After decapitation of the rats, trunk blood was obtained and the liver was removed to measure malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) and tissue factor (TF) activities and collagen content. Aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) activity were measured in the serum samples, while TNF-alpha and total antioxidant capacity were assayed in plasma samples. Results. Our results showed that MTX administration increased the hepatic MDA levels, MPO and TF activities and collagen contents and decreased GSH, while these alterations were reversed in resveratrol-treated group. Elevated AST and ALT activities ALT and TNF-alpha level observed following MTX treatment was depressed with resveratrol.. Conclusions. The present study showed that resveratrol protects against MTX-induced hepatic injury and may be of therapeutic potential in alleviating the systemic side effects of this chemotherapeutic agent.
Keywords: HUMAN-BLOOD; TRANS-RESVERATROL; FOLIC-ACID; TOXICITY; DEHYDROGENASES; MELATONIN; BIOPSIES; CELLS; LIVER; TIME